Krishna
0

Step 1: Apply the (a + b)(a - b) = a^2 - b^2 formula to the given equation

              EXAMPLE: (1 - \cos \theta)(1 + \cos \theta)(1 + \cot^2 \theta)


                                 (1^2 - \cos^2 \theta)(1 + \cot^2 \theta)


Step 2: Find the suitable trigonometric formula to simplify the equation

          EXAMPLE:   (1^2 - \cos^2 \theta)(1 + \cot^2 \theta)

                                          We know that \sin^2 \theta + \cos^2 \theta = 1

                                                                 \sin^2 \theta = 1 - \cos^2 \theta

                                                     And 1 + \cot^2 \theta = \cosec^2 \theta   


                            =   (\sin^2 \theta)( \cosec^2 \theta)


                            = (\sin^2 \theta)( \frac{1}{\sin^2 \theta}


                            = 1